PENGARUH BUDAYA ORGANISASI, DUKUNGAN MANAJEMEN PUNCAK, PELATIHAN DAN PENDIDIKAN TERHADAP APLIKASI TEKNOLOGI INFORMASI DAN PENGARUHNYA TERHADAP KINERJA RUMAH SAKIT DI PEKANBARU - Rachman, Abdul; Sari, Ria Nelly; Arifin, Kasman (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The study aims to test scientifically about the influence of organizational culture, topmanagement support, training and education of information technology applicationand its effect on hospital performance. Subjects in this study were directors, ITmanagers, financial managers, and other hospital management of 74 respondents.The data of this study were collected using several questionnaires such asinformation technology questionnaire, organizational culture, top managementsupport, training and education, organizational performance with total items as muchas 48 items. The technique used to analyze the data is Partial Least Squaretechnique using smartPLS 2.0 M3 program. The results of hypothesis testing of thisstudy resultd, the first the application of information technology affects theperformance of the company, with a value of T-statistics 15.727 (above 1.96).Second, organizational culture has an influence on the application of informationtechnology, with a value of T-statistics 2.899 (above 1.96). Third, top managementsupport influences the application of information technology with the value of Tstatistic2.834 (above 1,96). Fourth, training and education affect the application ofinformation technology with the value of T-Statistic 4.448 (above 1.96). The resultsof this study can be concluded that organizational culture, top management support,training, and education can affect the use of information technology and ultimatelyimpact on company performance.